Adults' responses to bullying: the victimized youth's perspectives. Issue 3 (4th May 2021) - Bjereld, Ylva; Daneback, Kristian; Mishna, Faye
ABSTRACT: Children are generally encouraged to tell adults about bullying. Although telling can be effective in ending bullying, adults do not necessarily respond in a way that is helpful. Previous research has rarely included victims' own thoughts and feelings regarding what adult actions and reactions are experienced as positive and helpful, and which are experienced as negative and unhelpful in managing bullying situations. This paper reports on interviews with bullied youth, with the overall aims of describing adults' responses to bullying from the victimized youth's perspectives and discussing how the youth experienced these responses. The analysis comprised grounded theory, emphasizing the victimized youth's points of view. When adults became aware of bullying, they responded in three ways; verbal, physical or avoiding/ignoring. Responses that included increasing adult presence were typically experienced as helpful, as were responses whereby the youth felt adults listened without blaming the victim for the bullying or, listened without excusing the behaviour of the youth that bullied. No response was depicted by the participants as unambiguously helpful although when adults avoided or ignored the bullying it was never helpful.